2017
DOI: 10.1007/s00068-017-0814-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of external fixation and locked intramedullary nailing in the treatment of femoral diaphysis fractures from gunshot injuries

Abstract: Level 3 retrospective comparative clinical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…The wound, fracture, and definitive fixation types were identified as significant predictors of outcomes in this study. Greater severity, complexity, and invasiveness of these factors were associated with increased odds of complications and poor functional outcomes, aligning with previous literature showing their importance in relation to infection, healing, stability, alignment, function, and quality of life in open proximal femoral fractures 9-12 . However, measuring and classifying these factors present certain limitations and challenges.…”
Section: Discussionsupporting
confidence: 86%
“…The wound, fracture, and definitive fixation types were identified as significant predictors of outcomes in this study. Greater severity, complexity, and invasiveness of these factors were associated with increased odds of complications and poor functional outcomes, aligning with previous literature showing their importance in relation to infection, healing, stability, alignment, function, and quality of life in open proximal femoral fractures 9-12 . However, measuring and classifying these factors present certain limitations and challenges.…”
Section: Discussionsupporting
confidence: 86%
“…The study concluded that infection was more related to the extent of damage than to the method of fixation and highlighted debridement. Polat [12] analysed 107 low energy diaphyseal femur fractures, comparing delayed external fixation and delayed nailing and no diferences were found between these methods. Nikolic [8] , analysing 41 subtrchanteric fractures in military, compared external fixation and plaster of Paris, finding high rate of complications in both.…”
Section: Resultsmentioning
confidence: 99%
“…The main limitation of these studies was the low level of evidence. In the present review, the study of Polat [12] performed a retrospective comparative study with 107 gunshot-induced femoral fractures in 99 patients and divided them into 2 groups, 1 treated with an intramedullary nailing and another with external fixation. The mean follow-up time was 76.3 months and no significant difference was observed in relation to the rates of postoperative complications.…”
Section: Setting Of Management and Complications In Low Energy Injuriesmentioning
confidence: 99%
“…Gunshot femur fractures Gustillo type I are quite prevalent and their treatment has some controversy. Polat [15] analyzed 107 low energy gunshot-induced diaphyseal femur…”
Section: Grade Iiicmentioning
confidence: 99%
“…Immediate fixation was performed in fractures of Grade 1 with infection rate equal to 0%. Polat [15] analyzed 107 grade I diaphysial femur fractures, comparing late external fixation and late fold, and no differences were found between these methods.…”
Section: Gustillo III Gunshot Fracturesmentioning
confidence: 99%